Naturalism, antinaturalism and meta-ethics - Woleński, Jan (Folia Philosophica, 2011)
The paper deals with dispute between naturalism and antinaturalism in meta-ethics. Different standpoints are discussed, especially those of cognitivism, non-cognitivism and emotivism, which leads to certain typology. The author introduces the category of bonitive statements, statements concerning the good, which logic is analogous to the one which determinates relations between deontic statemens. Generalized Hume’s argument on the axiological statements as impossible to be derived from non-axiological is concerned. In particular, it is argued that it does not support antinaturalistic thesis. The standpoint of axiological presentationism is proposed, which makes a link between non-cognitivism and the thesis according to which bonitive statements can be true or false and axiological presentationism can taken as a form of naturalism.